2006
DOI: 10.1007/s10750-006-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase activities of the aquatic moss Warnstorfia fluitans (Hedw.) Loeske from an acidic stream in North-East England

Abstract: A study was made of the aquatic environment, tissue nutrient composition and surface phosphatase activities of the aquatic moss Warnstorfia fluitans in Brandon Pithouse Stream, a small acidic stream in N-E England. The water, which originates from an underground spring, had been pH 2.6 for at least 30 years, but about 3.9 during the present study. The moss was by far the most abundant phototroph during all this period. Seasonal changes in aqueous nitrogen and phosphorus fractions were measured over a 2-year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
2
Order By: Relevance
“…The results of simple correlations and path analysis indicated that while increasing concentrations of both, plant-available and tissue P led to a signiWcant decrease in phosphatase activity, the direct eVect of plant-available P on enzyme activity was more signiWcant. Contrary to our results, Christmas and Whitton (1998) and Ellwood and Whitton (2007), who studied surface phosphatase activities in aquatic mosses, found the internal P concentration to be responsible for regulation of phosphatase activities, but no signiWcant correlation between phosphatase activity and water P. Similarly, Martinez-Crego et al (2006) reported a negative correlation between both root and leaf tissue P and extracellular phosphatase activities in seagrass, Posseidonia oceanica, but no relationship with P in water. The investigated mosses and seagrass came from environments, streams and a coastal sea meadow respectively, with water P Xuctuating more than in our mesocosm experiment.…”
Section: Enzyme Activity and Available Phosphoruscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of simple correlations and path analysis indicated that while increasing concentrations of both, plant-available and tissue P led to a signiWcant decrease in phosphatase activity, the direct eVect of plant-available P on enzyme activity was more signiWcant. Contrary to our results, Christmas and Whitton (1998) and Ellwood and Whitton (2007), who studied surface phosphatase activities in aquatic mosses, found the internal P concentration to be responsible for regulation of phosphatase activities, but no signiWcant correlation between phosphatase activity and water P. Similarly, Martinez-Crego et al (2006) reported a negative correlation between both root and leaf tissue P and extracellular phosphatase activities in seagrass, Posseidonia oceanica, but no relationship with P in water. The investigated mosses and seagrass came from environments, streams and a coastal sea meadow respectively, with water P Xuctuating more than in our mesocosm experiment.…”
Section: Enzyme Activity and Available Phosphoruscontrasting
confidence: 99%
“…This is in agreement with Johnson et al (1999) and Phoenix et al (2003) who found higher enzyme activities in Plantago lanceolata and several calcareous grassland species that were exposed to increased sediment nitrogen. Phoenix et al (2003) explained the stimulatory eVect of increased N availability on phosphatase activity by a phosphate starvation inducible type response-their results suggested that the expression of genes in the proposed phosphate starvation rescue system could be sensitive to shoot and soil N as well as P. An inverse relationship has been reported between tissue N and water/sediment P (Phoenix et al 2003, Ellwood andWhitton 2007). Similarly, Eleocharis and Typha in our experiment showed a signiWcant decrease in root tissue N with increasing P in the sediments (P = 0.003 and 0.016, respectively).…”
Section: Enzyme Activity and Nitrogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Such activity in aquatic phototrophs is usually induced under conditions of moderate P limitation and hence the rate of activity provides a measure of P limitation (Jansson et al, 1988;Christmas & Whitton, 1998a, b;Ellwood et al, 2002;Whitton et al 2005), though it may sometimes also reflect the fact that the only P source available is organic (Whitton et al, 1991;Ellwood & Whitton, 2007). It was therefore planned to compare changes in surface phosphatase activities of Didymosphenia in Stony Gill, North Yorkshire, during the main part of one growth season with concentrations of N and P fractions in the water.…”
Section: Introductionmentioning
confidence: 99%